Gaming addiction and sleep hygiene among young people - Francis Noel M. Carandang. 4 0 16; 5 (2019)
ABSTRACT: Video games has been around for a long time and these video games can somehow be addictive to the point where sleep quality is sacrificed for the sake of playing games. The present research was conducted in order to investigate what are the levels of gaming addiction, what are the levels of sleep deprivation among the respondents, and if there is any significant relationship between gaming addiction and sleep deprivation. To achieve these objectives, a total of 100 respondents were asked to answer two standardized tests through an online survey. The study made used of The Gaming Addiction Scale (GAS) and the The Adolescent Sleep Hygiene Scale revised (ASHSr) a self-report questionnaire. The result revealed that 44 percent of the respondents has a high gaming addiction, 10 percent has moderate addiction, 12 percent has low addiction, and 34 percent has no addiction, 45 percent has poor sleep hygiene and 55 percent has a good sleep hygiene. This findings indicate there is an addiciton among the respondents 45 percent engages in poor sleeping habits.
Undergraduate Thesis: (B.S. Psychology)- Pamantasan ng Lungsod ng Maynila, 2019.
Keywords: 2 -- 0; 6; 20; 20; 2